2016
DOI: 10.5194/gmd-9-4491-2016
|View full text |Cite
|
Sign up to set email alerts
|

StreamFlow 1.0: an extension to the spatially distributed snow model Alpine3D for hydrological modelling and deterministic stream temperature prediction

Abstract: Abstract. Climate change is expected to strongly impact the hydrological and thermal regimes of Alpine rivers within the coming decades. In this context, the development of hydrological models accounting for the specific dynamics of Alpine catchments appears as one of the promising approaches to reduce our uncertainty of future mountain hydrology. This paper describes the improvements brought to StreamFlow, an existing model for hydrological and stream temperature prediction built as an external extension to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 87 publications
3
40
0
Order By: Relevance
“…The streamflow from the Dischmabach is calculated using a spatially explicit and semi-distributed hydrologic response model that casts the soil moisture dynamics in a travel time distribution framework (Comola et al, 2015b;Gallice et al, 2016). Specifically, the model simulates hydrologic transport within subcatchment soil compartments and the stream network, identified through geomorphological analysis of the digital elevation model (Tarboton, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The streamflow from the Dischmabach is calculated using a spatially explicit and semi-distributed hydrologic response model that casts the soil moisture dynamics in a travel time distribution framework (Comola et al, 2015b;Gallice et al, 2016). Specifically, the model simulates hydrologic transport within subcatchment soil compartments and the stream network, identified through geomorphological analysis of the digital elevation model (Tarboton, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Here, the capabilities of Alpine3D to capture the soil moisture state is assessed. Furthermore, the Alpine3D model provides the surface scheme for a travel time distribution hydrologic response model to simulate catchment discharge (Comola et al, 2015b;Gallice et al, 2016) and here the role of soil moisture in the coupling of Alpine3D to the hydrologic response model, as well as the influence of the soil moisture state on streamflow generation in the catchment is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, two types of stream temperature models have been developed to date: regression models that make use of statistical linkages between meterological and geophysical conditions to predict stream temperatures (Benyahya et al, ; Jackson et al, , ; Mohseni et al, ) and mechanistic models based on conservation of energy that directly simulate the underlying stream temperature dynamics (Cox & Bolte, ; Loinaz et al, ; St‐Hilaire et al, ; see review by Dugdale et al, ). Mechanistic models usually demonstrate more clear cause‐effect relationships because of the direct descriptions of the underlying controlling processes in their governing equations (Caissie et al, ; Gallice et al, ; MacDonald et al, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the effectiveness of using the streambed thermal regime to quantify vertical water fluxes between the surface and subsurface domains (Anderson, ; Anibas et al, , ; Gordon et al, ; Vandersteen et al, ). Some mechanistic stream temperature models have incorporated the thermal advection and streambed conduction fluxes (Gallice et al, ; Haag & Luce, ; MacDonald et al, ). They considered the heat flux through the streambed as being propotional to the difference between stream surface water and streambed temperatures at a given depth (Moore et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation